Clinical Characteristics of Pediatric Coats' Disease With Retinal Cyst Using Wide-Angle Fluorescein Angiography - Liu, Jing-Hua; Deng, Guangda; Ma, Jing; Li, Liang; Fang, Yuxin; Li, Songfeng; Lu, Hai (Frontiers in Medicine, 2021)
Purpose: To assess the demographic and treatment features of pediatric patients of Coats’ disease with retinal cyst using wide-angle FA. Design: Retrospective, hospital based, cross-sectional study. Participants: Pediatric patients of Coats’ disease underwent wide-angle FA Methods: Retrospective review of pediatric patients of Coats’ disease underwent wide-angle FA at a single center from January,2015 to July,2020, demographic and treatment features were compared between patients with or without retinal cyst. Main Outcome Measures: Demographic and treatment outcomes Results: There were 123 pediatric Coats’ patients in our study, and 18.70% (23/123) of the patients complicated with retinal cyst, retinal cysts were mostly located in the inferior-temporal quadrant (73.9%, 17/23) and in the peripheral retina (82.6%,19/23). Compared with patients without retinal cyst, patients with retinal cyst had more clock-hours of telangiectasia on FA (7.32 vs 5.41, P=0.031), and may need more total treatments (7.47 vs 3.53, p=0.023) including laser photocoagulation (4.08 vs 2.31, p=0.019) or intravitreal anti-VEGF (3.13 vs 2.23, p=0.039), also longer time for telangiectasia resolution (22.33 months vs 18.53 months, p=0.043). Conclusion: Pediatric patients with Coats’ disease complicated with retinal cyst presented with more clock-hours of telangiectasia on FA and needed more total treatments and longer time for telangiectasia resolution.